Sociopreneurship to Reduce Extreme Poverty in the Coastal Areas of Pangkajene Islands: A Literature Review - Sylvia (Entrepreneurship and Small Business Research, 2022)
Pangkep has many natural resources due to its characteristics consisting of urban areas, highlands and islands. On the other hand, Pangkep is an area with a high level of extreme poverty. This poverty portrait can be found in four districts of Pangkajene Islands and the farthest island, 293 kilometers from Pangkep City. Sociopreneurship offers the concept of community empowerment so that they can rise from the downturn due to the economic problems faced by the coastal communities of the Pangkajene Islands. This study aims to formulate strategies for implementing sociopreneurship in the coastal areas of the Pangkajene Islands that are experiencing extreme poverty problems. This study used a qualitative research method with a literature review approach. This study found three sociopreneurship models: providing a place to sell SME products, developing tourist villages, and seeking investors for processing marine products. Strategies for implementing sociopreneurship include (1) running a sustainable business model, (2) running a coastal community empowerment program, (3) innovating products and services, (4) establishing partnerships and collaborations, (5) adopting a community-based approach, and (6) ) considering economies of scale and reproducibility.